2016
DOI: 10.1002/ece3.2676
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a salamander moving hybrid zone

Abstract: When related species meet upon postglacial range expansion, hybrid zones are frequently formed. Theory predicts that such zones may move over the landscape until equilibrium conditions are reached. One hybrid zone observed to be moving in historical times (1950–1979) is that of the pond‐breeding salamanders Triturus cristatus and Triturus marmoratus in western France. We identified the ecological correlates of the species hybrid zone as elevation, forestation, and hedgerows favoring the more terrestrial T. mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…This is higher than in most other areas studied (e.g. Wood et al 2003) but lower than what we observed in western France (Visser et al 2017). Moreover, new ponds are also being created, making this a dynamic system.…”
Section: Population Developmentscontrasting
confidence: 63%
“…This is higher than in most other areas studied (e.g. Wood et al 2003) but lower than what we observed in western France (Visser et al 2017). Moreover, new ponds are also being created, making this a dynamic system.…”
Section: Population Developmentscontrasting
confidence: 63%
“…This is in stark contrast with a T. cristatus x T. marmoratus hybrid zone in southwestern France where the hybridizing species are ecologically well differentiated. While T. marmoratus occupies mainly forested and hilly areas, T. cristatus is distributed in open and flat country (Schoorl & Zuiderwijk, ; Visser, Leeuw, Zuiderwijk, & Arntzen, ). Both species also reveal up to twice higher genetic divergence in comparison with T. cristatus and T. carnifex , a bimodal type of the hybrid zone with limited hybridization and introgression caused by strong postzygotic genomic incompatibilities (Arntzen, Jehle, Bardakci, Burke, & Wallis, ).…”
Section: Discussionmentioning
confidence: 99%
“…While several cases of moving hybrid zones have been documented, their prevalence is probably underestimated (Buggs, ; Wielstra et al., ). This is because the best way to characterize a moving hybrid zone is through the repeated study of predefined transects over different time periods, which is rarely feasible (Engebretsen, Barrow, Rittmeyer, Brown, & Moriarty Lemmon, ; Visser, de Leeuw, Zuiderwijk, & Arntzen, ). Additional insights can be obtained from the combination of cline and phylogeographical analyses on the distribution of alleles in the contact zone in a single time frame.…”
Section: Introductionmentioning
confidence: 99%